Commentary on Canonne (2018): Listening to Improvisation - Anglada-Tort, Manuel (Empirical Musicology Review, 2019)
The target study explores whether evaluations of the same piece of music differ under two distinct listening conditions: listening to a piece described either as an improvisation or as a preexisting composition. Participants (N = 16) in the two conditions listened to the same musical piece and provided verbal evaluative judgements. The author used a grounded theory approach to analyze listeners' responses, reporting different listening experiences in the two groups. The findings provide unique insights to enable a greater understanding of the nature of the aesthetics of improvisation. In this commentary, I first discuss the strengths of the article, followed by methodological considerations and suggestions for future research. I then present a short literature review and discussion of what I consider the most relevant topic in relation to this study, namely, the effects of contextual information on subjective evaluations.